DETECÇÃO DA MT1-MMP NA MUCOSA INTESTINAL DE RATOS E GALINHAS AO LONGO DO DESENVOLVIMENTO PRÉ E PÓS-NATAL - Camargo, Kamila Caroline (2013)
Membrane type I MMP (MT1-MMP) is involved in cellular adhesion, proliferation, migration and cell death during organogenesis and adult phase of vertebrates. However, its role in the development of the small intestinal has not been established. We formulated the hypothesis that this metalloproteinase would play a relevant role in the development of the intestinal mucosa. To assess this hypothesis was detected the labeling of MT1-MMP by immunohistochemistry in the intestinal mucosa along the pre-and postnatal development of rats and chickens so that from a comparative analysis, it were possible infer about the role of this metalloproteinase.In thepre natal phase of rats, the labeling of MT1-MMP correlates with events that lead to morphogenesis of villi and establishment of the tecidual homeostasis. In the pre natal phase of chickens, the labeling of MT1-MMP correlates with events that lead to growth of the intestine. In the postnatal phase of rats and chickens, the labeling of MT1-MMP was maintained in the intestinal mucosa, which led us to suggest that this metalloproteinase have a relevant role in the tecidual homeostasis throughout adulthood.We suggest that the role of that MT1-MMPin the remodeling and growth of the intestinal mucosa of rats and chickens is related with adhesion, proliferation, migration and death of epithelial cells and migration of mesenchymalcells. This is the first work that evidence the MT1-MMP in the small intestine of vertebrates during development, making it possible that further studies willclarify its role in the formation of this important organ.